DOES INTERNAL CONTROL WORK? FRAUD CASE IN GOVERNMENT SECTOR - INDONESIAN EVIDENCE - Hasnawati Hasnawati; Muhammad Nuryatno Amin (Media Riset Akuntansi, Auditing & Informasi, 2020)
This research analyzed the role of internal control in reducing intention to do fraud. Internal control becomes a variable that moderates the relationship between organizational culture, information asymmetry and law enforcement with a person's intention to commit fraud. This research took place in Sorong West Papua, a province in Eastern Indonesia. Respondents from this research are government employees and taken with convenience sampling method.The findings of this study are: This study proved that the greater the information asymmetry, the higher the intention to do fraud. In addition law enforcement and regulation could reduce fraud intention. However, this study had not proven the influence of organizational culture on fraud and this study also failed to prove the role of internal control to reduce fraud intentionThis research had a practical contribution where in this case, law enforcement and regulation becomes the most important thing in reducing fraud intention. Besides it is necessary to improve the internal control system in order to function as expected. The originality of this study, there are still little empirical research that discusses the study of internal control functions associated with the reduction of fraud intention.